Developing a Model for Successful Implementation of Customer Experience Management in Organizations: A Qualitative Study - Payam Mardazad Navi; Kambiz Heidarzadeh Hanzaee; Seyyed Buik Mohammadi; Mohsen Khoon Siavash (‫مدیریت بازرگانی)
Objective Building a strong customer experience is currently one of the most important management goals. The explosion of potential touch points and diminishing control over the customer experience requires companies to integrate multiple business functions such as IT, operations of the service, logistics, marketing, human resources, and even external partners and supply chains to create and deliver a positive customer experience. The purpose of this study is to provide a model of the key components that affect the successful implementation of customer experience management in the organization.